Revitalizing Tax Revenue: Tax Incentive Indonesia and Overcoming Negative Sentiment - Taqi, Muhamad; Rusydiana, Aam Slamet; As-Salafiyah, Aisyah; Kalbuana, Nawang; Mayyizah, Mamay (International Journal of Economics and Financial Issues, 2025)
This study aims to test the effectiveness of the Policy implemented by the Indonesian government to increase national tax revenues through tax incentive programs and solutions to negative sentiment and see the progress of research on “Tax Incentives in Indonesia” around the world published by journals on that theme. This research uses qualitative methods with bibliometric analysis and sentiment analysis approaches. The data used is secondary data with the theme “Tax Incentive Indonesia” from the Dimension database of 80 published journals. Then, the data is processed and analyzed using the VOSviewer application to know the bibliometric map of research development “Tax Incentive Indonesia” in this world. Apart from that, the data was also analyzed using the SentiStrength application to find out positive sentiment, negative, and neutral sentiment regarding the tax incentive policy that has been implemented in Indonesia. The results of the research found that the tax incentive program has proven effective in increasing national tax revenues and the solution to negative sentiment is to create activities that can increase taxpayers’ awareness of paying taxes, and trust in the government as well as direct benefit programs for taxes that have been paid. Then based on sentiment analysis, neutral sentiment is the highest result with a percentage of 50%, followed by positive and negative sentiment with each having a percentage of 25%. Meanwhile, based on bibliometric keyword mapping, 5 clusters can become research paths.